Measuring Social Performance in Social Enterprises: A Global Study of Microfinance Institutions - Leif Atle Beisland; Kwame Ohene Djan; Roy Mersland; Trond Randøy (Journal of Business Ethics, 2021)
Social enterprises in the microfinance industry need to adhere to both financial and social demands. Critics argue that there is a mission drift away from the social mission, and this has motivated the introduction of social rating agencies to strengthen the business ethics of microfinance institutions (MFIs). Using a global dataset of 204 socially rated MFIs from 58 countries, we assess the factors that drive the social performance ratings of MFIs. Overall our results show that social ratings of MFIs are significantly related to financial performance, greater outreach especially in rural areas, well-defined social objectives, staff commitment, service quality and an enhanced customer service. We observe that various rating agencies attach different importance to each of the social indicators. The public policy implication is that social rating agencies need to become more transparent, to reduce the information asymmetries between heterogenous socially motivated investors and the focal MFI.
Keywords: 650